Silicon-germanium (SiGe) nanostructures : production, properties and applications in electronics - Shiraki, Yasuhiro, 1942-; Usami, Noritaka (Philadelphia, PA : Woodhead Pub., 2011)
Annotation Nanostructured silicon-germanium (SiGe) opens up the prospects of novel and enhanced electronic device performance, especially for semiconductor devices. Silicon-germanium (SiGe) nanostructuresreviews the materials science of nanostructures and their properties and applications in different electronic devices. The introductory part one covers the structural properties of SiGe nanostructures, with a further chapter discussing electronic band structures of SiGe alloys. Part two concentrates on the formation of SiGe nanostructures, with chapters on different methods of crystal growth such as molecular beam epitaxy and chemical vapor deposition. This part also includes chapters covering strain engineering and modeling. Part three covers the material properties of SiGe nanostructures, including chapters on such topics as strain-induced defects, transport properties and microcavities and quantum cascade laser structures. In Part four, chapters cover ultra large scale integrated applications, MOSFETs and the use of SiGe in different types of transistors and optical devices -- Source other than Library of Congress.
Keywords: Nanostructured materials.; Silicon alloys.; Germanium alloys.; Electronic circuits.; Nanoelectronics.; elektronické knihy; electronic books